Validation of a prospective cohort study of older adults with hip fractures. (June 2019) - Metcalfe, D.; Costa, M. L.; Parsons, N. R.; Achten, J.; Masters, J.; Png, M. E.; Lamb, S. E.; Griffin, X. L.
Abstract : Aims: This study sought to determine the proportion of older adults with hip fractures captured by a multicentre prospective cohort, the World Hip Trauma Evaluation (WHiTE), whether there was evidence of selection bias during WHiTE recruitment, and the extent to which the WHiTE cohort is representative of the broader population of older adults with hip fractures. Patients and Methods: The characteristics of patients recruited into the WHiTE cohort study were compared with those treated at WHiTE hospitals during the same timeframe and submitted to the National Hip Fracture Database (NHFD). Results: Patients recruited to WHiTE were more likely to be admitted from their own home (83.5% vs 80.2%; p < 0.001) and to have a higher median Abbreviated Mental Test Score (AMTS) (9 (interquartile range (IQR) 6 to 10) vs 9 (IQR 5 to 10); p < 0.001) than those who were not recruited. In terms of WHiTE cohort generalizability, participating hospitals included a greater proportion of Major Trauma Centres (47.8% vs 7.8%) and large hospitals (997 (IQR 873 to 1290) vs 707 (459 to 903) beds) with high-volume Emergency Departments (median annual attendances of 43 981 (IQR 37 147 to 54 385) vs 35 964 (IQR 26 229 to 50 551)). However, there were few differences in baseline characteristics between patients in the WHiTE cohort and those recorded in the NHFD. Conclusion: There is evidence of a weak selection bias towards recruiting fitter patients within the WHiTE cohort, which will help to put into context the findings of future studies. We conclude that the patients within the WHiTE cohort are representative of the national population of older adults with hip fractures throughout England, Wales, and Northern Ireland. Cite this article: Bone Joint J 2019;101-B:708–714.